Analysis of Coconut Agribusiness Development Strategy in North Minahasa Regency - Rine Kaunang; Mellisa L. G. Taroreh; Charles R. Ngangi; Mukhlis Mukhlis (Postgraduate, University of Mataram, 2024)
The development of coconut in North Minahasa requires an appropriate and efficient strategy. This research aims to assess and analyze the conditions in the coconut agribusiness system in North Minahasa, outline the factors of IFAS (Internal Factors Analysis Summary) and EFAS (External Factors Analysis Summary) matrices, and provide policy recommendations related to the coconut agribusiness development strategy in North Minahasa. The research was conducted over a period of 9 months, utilizing both primary and secondary data. Primary data were obtained through the distribution of questionnaires, followed by Focus Group Discussions with respondents and direct interviews with coconut farmers, collector traders, and coconut processing industries (producing copra, flour, and coconut milk) in North Minahasa Regency, as well as business entities involved in the coconut agribusiness. Secondary data were obtained from relevant institutions such as the Central Statistics Agency, the Regional Agriculture Office of North Minahasa Regency, previous research journals, and related books. The research results, analyzed through a SWOT analysis of the Coconut Agribusiness Development Strategy in North Minahasa Regency, fall into quadrant I, indicating an aggressive strategy with coordinates (0.42:0.44), aligning with strengths and opportunities. The derived strategy is S-O (Strength-Opportunity), focusing on maintaining the availability of raw materials, the market for processed coconut products, human resources, and land suitability, with support from the local government to increase community income and expand coconut processed products into the international market.